2017
DOI: 10.3389/fimmu.2017.00325
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor Hobit Identifies Human Cytotoxic CD4+ T Cells

Abstract: The T cell lineage is commonly divided into CD4-expressing helper T cells that polarize immune responses through cytokine secretion and CD8-expressing cytotoxic T cells that eliminate infected target cells by virtue of the release of cytotoxic molecules. Recently, a population of CD4+ T cells that conforms to the phenotype of cytotoxic CD8+ T cells has received increased recognition. These cytotoxic CD4+ T cells display constitutive expression of granzyme B and perforin at the protein level and mediate HLA cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 28 publications
1
77
0
Order By: Relevance
“…1, B and C). ZNF683 has recently been shown to identify human CD4-CTLs (24), and Eomes and T-bet appear to be important in the development of CD4-CTLs (27, 28). These results confirm that human CD4-CTLs are highly enriched in the T EMRA subset.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1, B and C). ZNF683 has recently been shown to identify human CD4-CTLs (24), and Eomes and T-bet appear to be important in the development of CD4-CTLs (27, 28). These results confirm that human CD4-CTLs are highly enriched in the T EMRA subset.…”
Section: Resultsmentioning
confidence: 99%
“…4E). The role of ZNF683 (Hobit) (24, 46, 49) and other transcripts ( PRSS23 , SPON2 , and TCF7 ) (47, 48) in the survival and long-term persistence of these high cytotoxic terminal effector cells deserves further investigation (45). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously published that human Hobit is expressed in circulating populations of NK cells and antigen-experienced CD4 and CD8 T cells [20,34] in contrast to murine Hobit, which is specifically expressed in Trm and other resident lymphocytes including ILC1 and NKT cells [19]. We speculate that divergent evolutionary pressures by distinct mouse and human pathogens may have driven the unique expression patterns of Hobit in mice and humans.…”
Section: Discussionmentioning
confidence: 96%
“…However, it is also possible that CD4 þ CTLs may comprise a distinct, independent subset of CD4 þ effector T cells that differ from conventional Th1 cells (10). Indeed, several recent reports have identified specific markers for CD4 þ CTLs (11)(12)(13)(14). Interestingly, Eomes is expressed in many of the cells expressing these markers, as well as in other CD4 þ T cells with cytolytic properties (15)(16)(17)(18); these findings suggested that Eomes governs development of CD4 þ CTLs and that Eomes expression is a marker for CD4 þ CTLs.…”
mentioning
confidence: 99%